Processing and Preservation of Aquatic Products - Yin, Tao; Shi, Liu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Aquatic products are an important type of food, mainly including fish, shrimp, shellfish, crab, seaweed, etc. They provide human beings with high-quality protein, fatty acids, minerals, and other nutritional elements. Generally, aquatic raw materials need to go through transportation, processing, and preservation from the water area to the dining table. This Special Issue covers papers in the following areas: Advanced live fish transportation and quality change of aquatic products during transportation; New methods of processing on quality of aquatic products; New methods of preservation on shelf life and quality of aquatic products; Improvement of shelf life, nutrition, and quality of aquatic products; New detection, analysis, and management technology involved in transportation, processing, and preservation of aquatic products.